Pemenuhan Hak Ekonomi Sosial dan Budaya (EKOSOB) Bagi Masyarakat Nelayan di Kota Padang - Akmal, Akmal (Jurnal Demokrasi, 2011)
The aims of this research are to describe the aspects of social life of poor fishermen; to identify social intervention carried out by the government based on social condition of the fishermen; and find the violations toward economic, social, and cultural rights of the poor fishermen This study was conducted in some coast area of Padang. A qualitative approach has been used in this study. Based on data analysis, it is found that most of fishermen and their family could not access and get their economic, social, and cultural rights sufficiently. It seemed that government failed to meet their needs according to their human rights, especially the rights of economic, social, and cultural; moreover, it was indicated that violations have been frequently occurred toward their rights.Kata Kunci: Pemenuhan hak, Hak Asasi Manusia, Hak Ekosob, Masyarakat Nelayan